History of Rural Education and Pedagogy of Alternation: limits, challenges and possibilities in teacher training - Sebastião Silva Soares; Selva Guimarães (Universidade Federal do Norte do Tocantins, 2020)
This article propose a reflection on the limits and potentialities of the Alternation Pedagogy as an formative device in the process of teaching and learning in teacher education in the context of Countryside Education. We present a brief historical rescue on the Alternation Pedagogy and its integration in the curricula of the undergraduate courses in Countryside Education implemented in Brazil, through the Call for Selection n. 2/2012-Sesu/Setec/Secadi/MEC, of ​​August 31st of that year. According to the narratives of teacher trainers of two institutions contemplated by this public call in the Northern region of Brazil, we verify conceptions, limits, potentialities and future projections of Alternation Pedagogy.